Correlation between ultrasonographic and cytopathological findings obtained by fine needle aspiration biopsy in the evaluation of thyroid nodules (Brazilian Journal of Health Research, 2024)
Introduction: Thyroid nodules are prevalent, being identified by palpation in 4% to 7% of adult women and 1% of adult men and by ultrasonography (US) in 20% to 68% of patients. The incidence of thyroid cancer is approximately 24/100,000 population. It is important to define which nodule requires fine needle aspiration biopsy (FNAB) and which should be monitored. Objectives: To correlate the findings of the ultrasound aspects obtained by the TI-RADS classification with the data obtained by the cytopathological classification (Bethesda) of thyroid nodules that underwent FNAB. Methods: Retrospective, descriptive and cross-sectional study, in which the electronic medical records of ultrasound examination reports of patients with thyroid nodules and indication for FNAB were analyzed, in a clinic in Vitória/ES, between January/2023 and June/2023. Results: A total of 777 nodules in 659 patients (538 women and 121 men) were analyzed. The mean age was 51.94 years. Most nodules were larger than 1.0 cm and classified as TI-RADS 3 (74.5%), followed by classification 4 (14.5%), 2 (7.3%) and 5 (3.6%). An association was found between TI-RADS and the Bethesda classification (p
Keywords: Thyroid gland nodule; Thyroid gland; Thyroid Neoplasms; Needle biopsy; Ultrasound